Cancer Incidence and Mortality Survey in Wuwei, Gansu Province, Northwestern China from 2003 to 2012: A Retrospective Population-based Study - Li, Cheng-Yun (Chin Med J (Engl), 2016)
BACKGROUND: Population-based cancer registry collects the data on cancer incidence and mortality deaths from covered population to describe and survey the epidemics in certain areas. The aim of this study was to estimate the cancer incidence and mortality in Wuwei, Gansu province, Northwestern China from 2003 to 2012. The goal is to better understand cancer distribution and long-term development of cancer prevention and treatment in Wuwei. METHODS: Data were collected from the Wuwei Cancer Registry between 2003 and 2012. In this registry, data from 46 cancer report centers were included in this analysis. Incidence/mortality rates, age-specific incidence/mortality rates, age-standardized incidence/mortality rates, and cumulative incidence/mortality rates were calculated. Totally, 9,836,740 person-years (5,110,342 for males and 4,726,398 for females) had been monitored over this time period. The gender ratio of male/female was 1.08:1. The number of new cancer cases and related deaths was 24,705 and 17,287 from 2003 to 2012, respectively. RESULTS: The proportion of morphological verification was 74.43%. The incidence of cases identified through death certification only was 1.21%, and the mortality to incidence ratio was 0.70. The average crude incidence was 251.15/100,000 persons (310.61 and 186.87 for males and females per 100,000 persons, respectively). The age-standardized rates by Chinese standard population (ASR-China) and by world standard population (ASR-world) were 207.76 and 245.42 per 100,000 persons, respectively. The crude cancer mortality was 175.74/100,000 persons (228.34 and 118.86 for males and females per 100,000 persons). ASR for China and the world was 149.57 and 175.13/100,000 persons, respectively. The most common cancers and leading causes of cancer-related deaths in Wuwei were as follows: cancers of stomach, esophagus, liver, lung, colorectum, breast, cervix, lymphoma, blood (leukemia), brain, and central nervous system. In Wuwei, during 2003 and 2012, cancer incidence and mortality rates increased by 1.32% and 1.31%/year, respectively. During this time, colorectum cancer incidence and mortality rates increased by 2.69% and 7.54%/year, respectively, in Wuwei. The incidence and mortality of other gastric, esophageal, liver, and lung cancers also all increased. CONCLUSIONS: The results of this study report a more accurate cancer burden among the population of Wuwei, China. Active research of cancers etiology and effective prevention should be established to reduce the incidence and mortality associated with cancers.